THE REASON PEPSICO DOES NOT EXTEND THE COOPERATION CONTRACT WITH PT INDOFOOD SUKSES MAKMUR (INDF) FOR 2019-2021 - Lamanda "; Yessi Olivia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
PepsiCo Inc. Company is a multinational company originating from California, America that produces food and Beverage which is quite famous for its flagship product, Pepsi soda. whereas the company PT Indofood Sukses Makmur (INDF) is a local Indonesian company founded by the Salim Group and has become a trusted company in Indonesia, PT INDF is a company that is also manage products of food and beverage. The two companies cooperate in the form of a Joint Venture to produce PepsiCo brand products by establishing a factory in Purwakarta, Indonesia. This study discusses the beginning of the establishment, cooperation of company, and termination of ooperation between PepsiCo and PT INDF by using the joint venture theory and the theory of multinational companies based on the advantages and disadvantages of the parties to the joint venture, to prove the nalysis the researcher uses descriptive methods. The results in this study prove that PepsiCo's inability to compete in the food and beverage industry in Indonesia and suffer losses, especially competition with PT. Coca Cola Company as a similar company has a major impact on the termination of the joint venture. With this, PepsiCo no longer extends the Exclusive Bottling Agreement (EBA) with the expiration of this cooperation contract PepsiCo no longer produces its products in Indonesia, not only in beverage products but also stops producing snacks which are under the license of PT Indofood Fritolay Makmur (IFL). Keywords: multinational company, joint venture, food and beverage